1998
DOI: 10.1046/j.1365-2141.1998.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization and harvesting of peripheral blood stem cells: randomized evaluations of different doses of filgrastim

Abstract: Summary. The effects of different doses of filgrastim on yields of CD34þ peripheral blood stem cells were evaluated in patients with breast cancer. 55 were randomized to receive filgrastim 10, 20, 30 or 40 mg/kg/d with more CD34 þ cells/ kg/apheresis harvested after the three highest dose levels. 35 additional patients were randomized to receive 10 or 30 mg/ kg. The median number of CD34 þ cells collected after 10 mg/ kg (n ¼ 31) was 0·7 × 10 6 /kg/apheresis (range 0·1-4·4) as compared to 1·2 (range 0·1-6·8) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 31 publications
2
51
0
2
Order By: Relevance
“…Recently, a randomized study in patients showed that doses of 30 g/kg were more effective than 10 g/kg with only a minor increase in toxicity. 10 Our results are consistent with these latter observations, showing that the number of CD34 + cells collected with a single apheresis session with the 10 g/kg/12 h schedule is significantly higher than with 10 g/kg/24 h. The superiority of high doses of G-CSF could be explained by its pharmacokinetic profile.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, a randomized study in patients showed that doses of 30 g/kg were more effective than 10 g/kg with only a minor increase in toxicity. 10 Our results are consistent with these latter observations, showing that the number of CD34 + cells collected with a single apheresis session with the 10 g/kg/12 h schedule is significantly higher than with 10 g/kg/24 h. The superiority of high doses of G-CSF could be explained by its pharmacokinetic profile.…”
Section: Discussionsupporting
confidence: 92%
“…2,[7][8][9] Although experience with higher doses is limited, a recent report has suggested that they could be more effective with only a minor increase in toxicity. 10 Thus, the administration of high doses of G-CSF might enhance the quantity of stem cells collected, reducing the number of apheresis sessions and facilitating further graft manipulation such as T celldepletion (TCD) procedures. Moreover, recent reports suggest that the infusion of a large number of hematopoietic progenitor cells could improve the quality of engraftment and survival in allogeneic transplantation.…”
mentioning
confidence: 99%
“…As randomized trials have demonstrated the superiority of chemotherapy þ growth factors over growth factors alone, 17 we included only patients receiving both chemotherapy and G-CSF. Randomized trials have also suggested that the dose of G-CSF correlates with the mobilization efficiency when G-CSF is used alone 18 or following chemotherapy, 19 although the latter finding has not been consistent. 20 In our patient population, the G-CSF dose did not correlate with pCD34.…”
Section: Discussionmentioning
confidence: 99%
“…10 Factors influencing yields of progenitor cells for allogeneic transplantation have been recently discussed. 17 Luider et al 17 20 recently evaluated doses of filgrastim up to 40 g/kg/day but in an autologous setting in patients with breast cancer. In patients with good marrow reserves, doses of filgrastim greater than 10 g/kg/day yielded a higher number of CD34 ϩ cells and may be useful when high numbers of CD34 ϩ cells are required.…”
Section: Discussionmentioning
confidence: 99%